Pandemic Restrictions and Spatiotemporal Crime Patterns in New York, São Paulo, and Stockholm. (February 2022) - Ceccato, Vania; Kahn, Tulio; Herrmann, Christopher; Östlund, Anders
Studies are showing evidence of the effect of changes in routine activities due to the 2020 COVID-19 pandemic on crime levels in many cities worldwide. This study evaluates the potential impact of the COVID-19 pandemic on temporal and spatial patterns of crime in three major cities under very different national contexts. Each of the three countries and cities experienced different levels of pandemic restrictions and societal closure. The cities of New York (the United States), São Paulo (Brazil), and Stockholm (Sweden) were selected as cases. Temporal quantitative methods, spatial statistics techniques, and Geographical Information System (GIS) underlie the methodology used in this study. Findings show that there is a statistically significant break in the trend in crime levels after the stay-at-home orders were implemented in New York City, São Paulo, and Stockholm in the first months of 2020; the only exception was for murder. Such an impact varies by crime type and city context, but increases again after a few months, indicating how fast crime and criminals adapt. Residential burglary decreased, whereas nonresidential burglary increased overall. Changes in the levels and geography of vehicle thefts were observed, with an overall increase of significant cold spots but, in several cases, also solidification of existing crime concentrations in known crime attractors and in some deprived areas.